Perbandingan Analisis Prediksi Kebangkrutan Menggunakan Model Logistik Dan Model Kebangkrutan Bank Indonesia (Studi Empiris pada Bank yang Terdaftar di BEI) - Octaviani, Sri; Fathoni, Ahmad Fauzan; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to compare the both bankruptcy predict models between Logistic and Bank Indonesia bankruptcy model. We use secondary data in which get from Indonesian Capital Market Directory (ICMD). Purpose sampling is used to get the sample. T-test paired sample is used to analyse the data. The result shows that both of the models have different result in predicting of bankruptcy. Futhermore, we suggest to use Bank Indonesia bankruptcy model to predict bankruptcy because the result is more accurate than the Logistic model.Keywords: Logistic and Bank Indonesia bankruptcy model, bankruptcy